Prediction of mechanical response of hexagonal honeycomb SPS blast wall under explosive loading: In-depth review and empirical formula - Kim, Do Kyun; Looi, Chee Kean; Topa, Ameen; Cho, Nak Kyun (Ocean engineering, 2024)
Despite comprehensive prevention strategies, offshore operations consistently grapple with health, safety, and environmental (HSE) challenges. Though explosions on offshore structures are rare, their devastating impact cannot be understated. Blast walls, functioning as pivotal passive barriers, play a crucial role in protecting the topsides of these structures by dissipating explosive energy. Sandwich panel structures (SPS), with their lightweight attributes, enhanced bending rigidity and exceptional energy absorption, are a cost-effective countermeasure. This study introduces a groundbreaking design guideline, anchored in the LS-Dyna nonlinear finite-element method (NLFEM), tailored for hexagonal SPS offshore blast walls under explosive strains. Our rigorous numerical simulations, encompassing 450 varied scenarios, meticulously evaluated an array of geometric configurations and explosive strengths (spanning from 1 kg to 3 kg of TNT). From these simulations, crucial parameters affecting maximum mid-span plate deflection were discerned. In addition to these simulations, our research offers in-depth technical reviews, shedding light on the nuances of the subject. An empirical formula was subsequently formulated to anticipate this deflection, corroborating its efficacy by FE simulation outcomes. This work provides invaluable guidance for refining early-stage offshore blast wall design. •An in-depth technical reviews on the mechanical response of blast wall by sandwich panel system (SPS) is conducted.•A useful empirical formula is developed and can be utilised in the Pre-FEED stage in predicting the maximum deflection of the blast wall.•The proposed diagram may help to optimise the topside space of the offshore platform.